Evaluation of the effect of chronic pain on the functional and physical status of patients in older age groups - A. V. Naumov; T. M. Manevich; N. O. Khovasova; V. I. Moroz; A. D. Meshkov; D. V. Demenok; A. A. Malysheva (Современная ревматология, 2021)
Objective: to assess the structure and influence of chronic pain (CP) on the functional status of patients with geriatric syndromes.Patients and methods. The study included 370 geriatric patients who were divided into two groups. Group A included 300 patients (mean age 75.1±8.25 years) with CP, and group B – 70 subjects of comparable age (75.1±7.75 years) without CP. All study participants were found to have polymorbidity: the Charlson index was 5.55±1.59 points in group A and 5.56±1.64 points in group B (p=0.963). All patients underwent a comprehensive geriatric assessment (CGE) to determine the functional status and diagnose geriatric syndromes.Results and discussion. According to the CGE data, senile asthenia syndrome was detected in 127 (42.3%) patients with CP and in 20 (28.6%) patients without CP (p=0.035). The average number of geriatric syndromes in group A was 7.06±2.68, in group B – 5.2±1.8 (p<0.001).Group A patients differed from those without CP in a significantly higher degree of dependence in daily life (Bartel index) and a lower score on the Physical Performance Battery.Conclusion. Patients with CP have poorer physical functioning and a greater degree of dependence on others in their daily life. When planning the most effective complex strategies for the treatment and prevention of CP exacerbations, it is necessary to take into account the functional status of elderly patients.